Science In The Development Of Islamic Education: Dialectics of Muslim Scientific Thought - Sumadi, Eko (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2023)
Islamic education is still understood traditionally as containing the sciences of tafaqquh fiddin. On the other hand, science is still considered a separate scientific discipline from Islamic Education. This study aims to explain and analyze the dialectics of scientists regarding Islamic Science and the urgency of science for the development of Islamic Education. This article is the result of a systematic literature review through the identification, evaluation and synthesis of the thoughts of Muslim scientists. This study concluded that science education is the peak achievement of Muslims' dialectic towards science. Science education is necessary for Islamic education, which will provide a way forward towards the revival of Islamic civilization—namely, science that uses metaphysics in an Islamic perspective to guide in formulating concepts about the universe. Finally, science education will only be realized if scientists and religionists have a harmonious relationship. So, it is necessary to create a dialogical, pluralist and democratic climate so science education can grow and run well.